Do the elderly raise different issues when using the Patient Concerns Inventory in routine head and neck cancer follow‐up clinics?. (4th February 2015) - Rogers, S.N.; Audisio, R.A.; Lowe, D.
<x xml:space="preserve">Abstract</x> Head and Neck (H&N) cancer treatment can have a major detrimental impact on patient lives, and these issues can go unrecognised and be inadequately addressed. The aim of this paper is to compare the Patient Concerns Inventory (PCI) responses across age groups attending routine H&N cancer follow‐up clinics with particular focus on the elderly (75 years or older). The PCI‐HN data were obtained from patients attending follow‐up clinics between August 2007 and January 2013. The groups for comparison were: <55 (n = 105), 55–64 (n = 170), 65–69 (n = 64), 70–74 (n = 68), and ≥75 (n = 76), the median in this last group of 79.1 years. Regarding quality of life (QoL) on first completing the PCI the elderly reported better anxiety and mood, higher social‐emotional subscale scores and better overall QoL. On the PCI, being elderly did not seem to affect the total numbers of items selected, though fewer items were selected from the psychological, emotional and spiritual well‐being domain, and in particular the item about fear of recurrence. Dentist and surgeon were the two health professionals most often selected that patients wished to see or be referred on to. It is possible to recognise concerns in routine clinical care, thus allowing the opportunity for intervention and support to improve the outcome for the elderly.